Developmental Assessment As Basic Strategies In Developingprereading Skills Of Children With Special Needs Preschool - Susilawati, Sinta Yuni; Earlyarini, Riyanda Putri; Ummah, Umi Safiul; Novianti, Ranti; Anisa, Nur; Viorella, Nanda; Nirmala, Theresia (Proceedings Series of Educational Studies, 2024)
Developing reading skills in preschool children with special needs, particularly those with hearingimpairments, presents unique challenges. Assessment is crucial in understanding each child's characteristics, behaviors, and program effectiveness, guiding the creation of tailored strategies. This study focuses on using developmental progress assessments as a strategy to enhance pre- reading skills in preschool children with hearing impairments. The research aimed to understandthe pre-reading abilities of these children and design strategies to develop these skills basedonassessment results. A mixed-methods approach was used, combining qualitative and quantitativemethods in a multistage evaluation design. The research was conducted in three phases: 1) Preliminary study to gather initial data and create a draft strategy, 2) Development phaseincluding field trials, feasibility tests, and expert validation, and 3) Effectiveness testing of thedeveloped strategy. Data were collected through interviews, documentation